Bioactivity and nutritional quality of nutgall (Rhus semialata Murray), an underutilized fruit of Manipur - Singh, Thangjam Surchandra; Kshetri, Pintubala; Devi, Asem Kajal; Langamba, Pangambam; Tamreihao, Keishing; Singh, Heikham Naresh; Akoijam, Romila; Chongtham, Tania; Devi, Chingakham Premabati; Singh, Tensubam Basanta; Chongtham, Sonia; Devi, Yumnam Prabhabati; et al. (Frontiers in Nutrition, 2023)
Introduction Underutilized fruits plays a significant role in socio economic, cultural, nutritional and ethnomedicinal status of tribal people. However, scientific studies on the nutritional and other pharmaceuticals/biological activities of these fruits are meagre. Hence, the present study dealt with the quantification of nutritional quality and deciphering the bioactivity of nutgall (Rhus semialata Murray syn. Rhus chinensis Mill.), an underutilized fruit crop mainly found in foothill tracks of Eastern Himalaya, India, China, Japan, Korea and other South East Asian countries. Methods The Rhus semialata Murray fruits were collected from five different locations in Purul sub-division, Senapati district, Manipur, India. The nutritional composition of the fruit pulp was analysed. Further the fruit pulp was extracted in methanol and water. The methanol and water extracts were studied for bioactivity properties such as antioxidant, antihyperglycemic, antihypertensive, antihyperuricemia, anti-tyrosinase, and antimicrobial activity. Results and discussion The fruit was rich in essential fatty acids. The presence of linoleic and oleic acids, along with traces of docosahexaenoic acid and eicosapantaenoic acid, revealed the potential food value of the fruit. 59.18% of the total amino acid composition of the protein present was constituted by essential amino acids. The IC50 value of methanolic extract (MExt) and Water extract (WExt) of the fruit were recorded as 4.05 ± 0.22 and 4.45 ± 0.16 μg/mL, respectively, in the DPPH assay and 5.43 ± 0.37 and 11.36 ± 2.9 μg/mL, respectively, in the ABTS assay as compared to Ascorbic acid (3 and 5.4 μg/mL in DPPH and ABTS assay, respectively). The CUPRAC assay also showed a high antioxidant potential of MExt and WExt (1143.84 ± 88.34 and 456.53 ± 30.02 mg Ascorbic Acid Equivalent/g, respectively). MExt and WExt of the fruit were more active against α-glucosidase (IC50 of 1.61 ± 0.34 and 7.74 ± 0.54 μg/ mL, respectively) than α-amylase enzyme (IC50 14.15 ± 0.57 and 123.33 ± 14.7 μg/mL, respectively). In addition, the methanolic fruit extract showed low to moderate pharmacological potential in terms of antihypertensive (Angiotensin converting enzyme-I inhibition), antihyperuricemia (xanthine oxidase inhibition), anti-tyrosinase, and antimicrobial activity. The IC50 values of angiotensin-converting enzyme I inhibition, xanthine oxidase inhibition and tyrosinase inhibition were recorded as 13.35 ± 1.21 mg/mL, 93.16 ± 4.65 mg/mL, and 862.7 ± 12.62 μg/mL, respectively. The study evidently indicates that nutgall fruit is a potential source of phytonutrients, bestowed with commercially exploitable, multifaceted health benefits